PENDISIPLINAN DAN PENGAWASAN TUBUH MELALUI TATA RIAS WAJAH BAGI PEKERJA PEREMPUAN - , Indah Wenerda ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research entitled The Discipline and Surveillance of the Body through Make-Up for Women Workers is conducted to Telkomsel workers positioned as customer service. Overall, Telkomsel workers have body discipline at work. In its implementation, the discipline goes along with surveillance continuously. The discipline for those positioned as customer service is very strict especially for women workers. They have discipline of body through practice of make-up which has its own standard. The make-up standard is listed in guidebook given when training time. The standard is made by the company for women customer service according to ideal characteristics of women which develop in Indonesian society. Those characteristics about womanâs inferiority to the body especially womanâs beauty are represented by facial make-up. This discourse is inevitable with ideology of patriarchy in Indonesia. Make-up standard for women workers as customer service is a kind of discourse reproduction by the company, Telkomsel, related to discourse of womanâs inferiority to her body. The company as power manage uses make-up standard for its women workers at work. Women customer service must understand this rule and realize that her faces are important assets while working, so the face needs special methods of treatment and make-up to achieve the company standard. Discipline of body for women customer service is the discipline of body which is actually not relevant to her work function as customer service. The company is just using make-up as positive mechanism for either women workers or company image. Make-up becomes positive mechanism for women workers for beauty pleasure, while for the company, it is a politic of body technologies in order to be productive and subjected. Women customer service bodies through her faces become area of exercising power relation by the company, Telkomsel, in capital accumulation, but not forever as a customer service position is always subordinate to the power of the object because there is resistance from their efforts when the exercising power takes place.